2005
DOI: 10.1177/000312240507000306
|View full text |Cite
|
Sign up to set email alerts
|

Sovereignty Relinquished? Explaining Commitment to the International Human Rights Covenants, 1966-1999

Abstract: This article examines whether the content of the International Human Rights Covenants and the costs associated with their ratification influence the decision of countries to join. The author evaluates three theoretical perspectives-rationalism, world polity institutionalism, and the clash of civilizations-with data for more than 130 countries between 1966 and 1999. Rationalists contend that treaty ratification is tightly coupled with internal sovereignty arrangements, human rights practices, and ideological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
181
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(183 citation statements)
references
References 47 publications
1
181
0
1
Order By: Relevance
“…In large part replacing formerly legitimated states and corporate groups as primordially constitutive structures, the postwar world saw the striking rise in global principles of the human rights of all individual persons (Soysal 1994, Lauren 2003, Cole 2005, Stacy 2009). Even before the end of the war, the leaders of racist United States and imperialist United Kingdom agreed in an Atlantic Charter on principles of universal human rights that would undercut both polities.…”
Section: Ontology: Constructing the Person As Primordial Actormentioning
confidence: 99%
See 1 more Smart Citation
“…In large part replacing formerly legitimated states and corporate groups as primordially constitutive structures, the postwar world saw the striking rise in global principles of the human rights of all individual persons (Soysal 1994, Lauren 2003, Cole 2005, Stacy 2009). Even before the end of the war, the leaders of racist United States and imperialist United Kingdom agreed in an Atlantic Charter on principles of universal human rights that would undercut both polities.…”
Section: Ontology: Constructing the Person As Primordial Actormentioning
confidence: 99%
“…At the organizational level, there are the great gaps between structures and practices (Dalton 1959) or formal and informal structures. At the nation-state level, disconnections between policies and practices are extreme (e.g., Hathaway 2002, Hafner-Burton & Tsutsui 2005, Cole 2005). In theories taking the realist form of action theory, activity is chosen by agentic purposive actors, so great inconsistencies are difficult to explain (economic theory tends to rule them out by definition).…”
Section: Decoupling: the Relation Between Actor Identity And Practicementioning
confidence: 99%
“…Institutional sociology touts the power of "world society" to generate and diffuse norms of behavior that mimic accepted scripts of modernity -encouraging countries on the periphery to display outward forms in conformity with the institutions and forms of leading states of the western world -without internalizing the values behind these forms. The theory predicts a "radical decoupling" of treaty commitments, which are said to be "expected" of all modern states, from actual rights behaviors (Cole 2005;Wotipka & Ramirez 2008).…”
Section: Human Rightsmentioning
confidence: 99%
“…Previous research has demonstrated the importance of international forces to country-level ratification of human rights treaties (Cole 2005), to the creation of gender mainstreaming offices (True and Mintrom 2001), and to the adoption of equal pay legislation (Berkovitch 1999b). But state-level promises can easily be "decoupled" from actual practice (Cole 2005). For example, Saudi Arabia's ratification of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) belies its opposition to female suffrage.…”
mentioning
confidence: 99%